Metode Latihan Based Small Side Games Terhadap Akurasi Passing Pada Ekstrakulikuler SMPN 224jAKARTA - Azka, Muhammad azka Ainun Naim; Gustiawati, Resty; Kusuma Yuda, Aria (Universitas Hamzanwadi, 2024)
The problem in this study is that the average of each student in making passing errors is 20 times. Students often fail to direct the ball to their own friends. The boring training method makes students less enthusiastic in participating in passing training. This study aims to examine the effect of the method based small side games on passing accuracy in extracurricular activities. This research was conducted at SMPN 224 Jakarta with 30 students. The type of quantitative research is experimental, the method used in this research is the experimental method of one group pretest posttest design. Based on the research results obtained t test results with a t value of 9.406 and a t table value of 2.045. The calculated t value obtained is greater than the t table, 9.406 > 2.045), meaning that there is a difference in improvement between the pretest and posttest. From the difference between the average pretest and posttest, it can be seen that the percentage increase is 60.96%. This means that small sided games training has an influence of 60.96% on the passing skills of extracurricular student participants.